Impact of Palliative Care/Medicine on Realization of "Right to Life" and "Right to Dignity" in The Context of Human Rights Protection - Titko, Elvira; Dei, Maryna; Smalii, Oleksandr; Yuldashev, Serhiy (Journal of History Culture and Art Research, 2020)
This study aims to define the content, interpretation and understanding of palliative care / medicine in the context of the development of modern biomedicine with the priority of the role of protection and respect for human rights, while focusing on the categories of seriously ill and their implementation of "the right to life", "the right to health", and "The right to death". The study was conducted on the basis of the analysis of normative legal acts, jurisprudence, relevant scientific and statistical data that regulate the issues of palliative and hospice care, euthanasia and their interconnection. Comparative palliative care in different countries was based on theoretical sources, legislation of the countries and the "Quality of Death Index". The overview of the laws of the world was done and it was found that the country in which the euthanasia is legally possible; countries where it is not prohibited and the countries criminal law which establishes the prohibition of euthanasia with further punishment for its implementation. The statistics of recent years show that the majority of diseases, which in the future lead to incurable diseases, in which both patients and relatives find themselves in the path of despair and fear. In such circumstances the need for palliative care constantly ascending aye. In this context, questions arise as to the understanding of the nature of palliative care / medicine as a combination of therapeutic measures or a decent completion of life linking these two areas with the realization of such rights as the right to life, health, and death. In the context of the latter, the understanding of the role and place of euthanasia is becoming apparent not only for the severely ill, but also for healthy people, based on the desire for a decent completion of life and the impossibility of committing suicide, which is a punishable act. That is why the importance of palliative care/medicine is necessary, first of all, from the legal point of view and the protection of human rights, which is the priority of every democratic state. In the study, it was concluded that palliative care/medicine must have a clear understanding and legal consolidation at both the international and national levels, based on the concept of essence "pain" through a set of measures to right ted for rehabilitation or worthy end of life, in a speech last activity search effective ways to avoid future life-threatening cases. Therefore, palliative aid/medicine serves some basis for the rights to a decent life worthy of death of people with the prospect of an overall strategy of healthy and decent life for future generations.